2014
DOI: 10.1038/ncomms6253
|View full text |Cite
|
Sign up to set email alerts
|

Small palladium islands embedded in palladium–tungsten bimetallic nanoparticles form catalytic hotspots for oxygen reduction

Abstract: The sluggish kinetics of the oxygen reduction reaction at the cathode side of proton exchange membrane fuel cells is one major technical challenge for realizing sustainable solutions for the transportation sector. Finding efficient yet cheap electrocatalysts to speed up this reaction therefore motivates researchers all over the world. Here we demonstrate an efficient synthesis of palladium-tungsten bimetallic nanoparticles supported on ordered mesoporous carbon. Despite a very low percentage of noble metal (pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 51 publications
0
64
0
Order By: Relevance
“…deposited silver–palladium core–shell alloy nanoparticles (diameter: 7.5 nm) onto multiwall carbon nanotubes and observed an onset potential of oxygen reduction around +0.9 V versus RHE and an n value of about 3. In another study, Hu et al . decorated ordered mesoporous carbons with palladium–tungsten alloy nanoparticles that featured segregated nanoislands of palladium (ca.…”
Section: Resultsmentioning
confidence: 99%
“…deposited silver–palladium core–shell alloy nanoparticles (diameter: 7.5 nm) onto multiwall carbon nanotubes and observed an onset potential of oxygen reduction around +0.9 V versus RHE and an n value of about 3. In another study, Hu et al . decorated ordered mesoporous carbons with palladium–tungsten alloy nanoparticles that featured segregated nanoislands of palladium (ca.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the synthesis of NPs composed of two elements (bi-NPs) has stimulated research efforts [8][9][10][11][12][13] due to their remarkably enhanced catalytic, microbicidal, optical, electronic, and mechanical properties, which goes beyond the mere sum of the effects of the constituent materials. Ag/Fe a Author to whom correspondence should be addressed.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…9 Small quantities of Pd inside Pd-W NPs metal are sufficient to enhance the cluster stability and catalytic properties due to the formation of ultra-active Pd hot-spots. 10 Moreover, Ag can broaden the bactericidal activity of TiO 2 -based photocatalyst composite materials and can also act against silver-resistant microorganisms due to their photooxidative mechanism, 14 and various wet synthesis methods have been used resulting in Ag decoration of TiO 2 nanostructures. [15][16][17][18] However, very little is known about the formation and properties of bi-NPs-based coatings.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…From DFT calculations it is commonly modeled that the active site for the oxygen reduction in both acidic and alkaline medium is the central metal atom. In alkaline medium the ORR process is represented by the scheme leftI) +normalO2g+normalH2normalO(l)+normaleOOH+normalOHII) OOH+normaleO+normalOHIII) O+normalH2normalO(l)+normaleOH+normalOHIV) OH+normalenormalOH+ where the * represents the active site (cobalt). It was shown that the rate limiting steps in the scheme above were the formation of *OOH and OH − (steps I and IV).…”
Section: Cobalt‐based Electrocatalystsmentioning
confidence: 99%